Intestinal fungal dysbiosis and systemic immune response to fungi in patients with alcoholic hepatitis - Lang, Sonja (Hepatology, 2019)
Chronic alcohol consumption causes increased intestinal permeability and changes in the intestinal microbiota composition which contribute to the development and progression of alcohol-related liver disease. In this setting, little is known about commensal fungi in the gut. We studied the intestinal mycobiota in a cohort of patients with alcoholic hepatitis, patients with alcohol use disorder and non-alcoholic controls using fungal-specific internal transcribed spacer (ITS) amplicon sequencing of fecal samples. We further measured serum anti–Saccharomyces cerevisiae antibodies (ASCA) as systemic immune response to fungal products or fungi. Candida was the most abundant genus in the fecal mycobiota of the two alcohol groups whereas genus Penicillium dominated the mycobiome of non-alcoholic controls. We observed a lower diversity in the alcohol groups compared to controls. Antibiotic or steroid treatment was not associated with a lower diversity. Patients with alcoholic hepatitis had significantly higher ASCA levels compared to patients with alcohol use disorder and to non-alcoholic controls. Within the alcoholic hepatitis patient cohort, patients with levels of ≥34 IU/ml, had a significantly lower 90-day survival (60%) compared to those with ASCA levels <34 IU/ml (80%) with an adjusted hazard ratio of 3.13 (95% CI 1.11–8.82, p=0.031). In conclusion, patients with alcohol-associated liver disease have a lower fungal diversity with an overgrowth of Candida compared to controls. Higher serum ASCA was associated with increased mortality in alcoholic hepatitis patients. Intestinal fungi may serve as a therapeutic target to improve survival and ASCA may be useful to predict the outcome in patients with alcoholic hepatitis.